(untitled) (Contemporary Issues in Social Sciences and Management Practices, 2024)
This study investigates the influence of digital media and brand trust on consumer purchase intentions, with a specific focus on the mediating role of consumer engagement in the textile industry. As digital media becomes a primary platform for brand-consumer interactions, understanding how it shapes consumer behavior is crucial. Grounded in quantitative research, the study surveyed 300 consumers of a well-known textile brand to examine the interconnected roles of digital media influence, brand trust, and consumer engagement. Findings revealed that digital media enhances brand visibility and interaction, but its effectiveness in fostering purchase intentions relies heavily on trust and engagement. Brand trust emerged as essential for reducing perceived risks and encouraging consumer loyalty, while consumer engagement was found to mediate the relationship between digital media and purchase intentions, creating a bridge that deepens brand-consumer bonds. This study’s integrated approach underscores the importance of developing cohesive digital marketing strategies that not only attract consumers but also build trust and active engagement. The research provides valuable insights for brands in the textile industry and similar sectors, demonstrating that a comprehensive approach combining digital media, trust-building, and engagement fosters stronger consumer relationships and higher purchase intentions.